Competition Stress Leads to a Blunting of the Cortisol Awakening Response in Elite Rowers - MacDonald, Douglas; Wetherell, Mark A. (Frontiers in Psychology, 2019)
Background Anticipation of forthcoming demands is often met with biological up-regulation, for example, levels of the stress hormone cortisol are typically elevated immediately prior to an anticipated event. Similarly, the Cortisol Awakening Response (CAR), a surge in cortisol in the period following waking, is elevated on days of anticipated demand and this is viewed as an adaptive response in the preparation for challenge. This study assessed the effects of competition as an anticipated challenge in elite rowers. Methods Elite rowers (N=8) were assessed during two training and two competition weekends. Each assessment involved the measurement of self-reported competitive (cognitive and somatic) anxiety and salivary diurnal cortisol across two days representing a preparation day prior to either a training or competition day. Competitive anxiety was measured each morning and saliva samples were provided immediately upon waking and 30 minutes post waking (CAR) and before bed. Results Self-reported cognitive and somatic anxiety were significantly greater during the competition phase compared with training. Additionally, levels of cognitive anxiety were greater on the day of competition compared with the preparation day. CAR magnitude was significantly reduced during the competition phase compared with training; however, there were no differences between preparation and event days. Conclusions Blunted CARs are typically observed in chronically stressed populations and are characteristic of burnout and fatigue. While an increased CAR during competition may represent an adaptive response to challenge, blunted CARs and concomitant increases in competitive anxiety indicate maladaptive responding during a period where maximised functioning is critical.